Implementasi Praktik Fasilitatif Keimigrasian Dalam Pengelolaan Barang Milik Negara Upaya Mewujudkan Tata Kelola Aset Yang Transparan Dan Akuntabel - Annan Tri Baihaqi; Benni Eksaudi Hasiholan Sinaga; Daffi Aditya Rayhan; Elvira Rossi; Lala Rafella (Jurnal Ekonomi dan Bisnis Digital, 2025)
The management of State-Owned Assets (Barang Milik Negara/BMN) within government institutions, including the Directorate General of Immigration, plays a crucial role in achieving transparent and accountable governance in line with the principles of good governance. The implementation of facilitative practices in immigration-related asset management serves as an effort to bridge institutional operational needs with existing regulations, thereby creating an orderly, efficient, and sustainable asset management system. This study aims to explore how facilitative practices in immigration are applied to support the management of BMN, particularly in terms of utilization, maintenance, and supervision of state assets. The research employs a qualitative descriptive method, combining regulatory analysis, field observations, and literature review. The findings indicate that facilitative practices enhance the effectiveness of BMN management through procedural simplification, transparent documentation, and accountable reporting. Thus, the implementation of facilitative immigration practices can be regarded as a key strategy to strengthen integrity in state asset management while fostering professional governance that prioritizes public service.